Синтактико-семантические особенности русских и словацких языковых афоризмов - Gallo, Ján (Studia Rossica Posnaniensia, 2020)
The article compares/contrasts the syntactic and semantic features of language aphorisms in Russian and Slovak. The Russian and Slovak language aphorisms have a priori axiological modality and are capable of referemental use, as potential acts of motivation and acts of affirmation. The expediency of this analysis is due to the fact that the illocutionary force has national and cultural specifics, which is manifested at all levels of language, speech and discourse. The object of the article is Russian and Slovak proverbs, sayings and winged expressions, in which the value bases of interpersonal speech communication are focused. A group of examples of the greatest illocutionary force is given, i.e. speech acts of prompting, then affirmative speech acts, as well as speech acts of inducement and affirmations that acquire additional illocutionary power. The taxonomy of the illocutionary force contained in Russian and Slovak folk aphorisms takes the following outlines: a) the most illocutionary power is speech acts of motivation, in which proverbs are used; b) affirmative speech and behavioral acts, which are evaluative aphorisms, have the status of passing thoughts with a light touch of lax edification, warning, or wish, and therefore, their illocutionary force is less pronounced; c) speech acts of inducement and affirmation acquire additional illocutionary force if the proverbs used in them retain the connotation of an authoritative original source. In the last part of the text, conclusions of the presented issue are drawn.